Blind spots in stigma research? Broadening our perspective on mental illness stigma by exploring 'what matters most' in modern Western societies. (17th March 2021) - Schomerus, G.; Angermeyer, M. C.
Abstract: Aims: The theory of 'what matters most' (WMM) has been developed to understand differences in mental illness stigma between cultures, postulating that stigma becomes most pervasive in situations that matter most in a specific cultural context. The rise of populism in Western societies demonstrates that also within one cultural context, different values 'matter most' to different groups. We expand the WMM framework to explore the spectrum of stigma manifestations within Western societies, relating it to both conservative/authoritarian and liberal/modern values. From our findings, we will develop hypotheses on how further research into value orientations and stigma might address potential blind spots in stigma research. Methods: Based on a narrative review of the literature on mental illness stigma and value orientations, we apply the WMM framework to cultural mechanisms of stigma within modern Western societies. Results: There are several studies showing an association between traditional, authoritarian, conservative values with stronger mental illness stigma, while studies examining the stigma within liberal, modern value orientations are scarce. We hypothesise on situations where encountering a person with mental illness could threaten liberal values and thus might provoke stigma among persons with such value orientations. For example, living with a person with mental illness could be seen as consuming energy and time, thereby jeopardising 'self-actualisation', the modern value of realising one's own full potential. As a result, a person highly valuing self-actualisation might try to avoid contact with persons with mental illness. Instances of potential 'liberal stigma' also include structural stigma or self-stigma, when, e.g. changing assumptions of what is considered 'normal' increase perceptions of being fundamentally different when experiencing mental illness. Conclusions: 'WMM' appears to be a useful framework to direct research to potential blind spots within the field of stigma research. Looking at instances where liberal values conflict with dealing with a person with mental illness could provide a more comprehensive understanding of stigma experiences among persons with mental illness. However, for measuring stigma, tapping into liberal variations of mental illness stigma is methodologically challenging. Qualitative work could be the first step to elicit potential stigma experiences based on conflicts with liberal values.